Vaccine-mediated immune responses to experimental pulmonary Cryptococcus gattii infection in mice. - Ashok K Chaturvedi; Rumanasma S Hameed; Karen L Wozniak; Camaron R Hole; Chrissy M Leopold Wager; Susan T Weintraub; Jose L Lopez-Ribot; Floyd L Wormley (PLoS ONE, 2014)
Cryptococcus gattii is a fungal pathogen that can cause life-threatening respiratory and disseminated infections in immune-competent and immune-suppressed individuals. Currently, there are no standardized vaccines against cryptococcosis in humans, underlying an urgent need for effective therapies and/or vaccines. In this study, we evaluated the efficacy of intranasal immunization with C. gattii cell wall associated (CW) and/or cytoplasmic (CP) protein preparations to induce protection against experimental pulmonary C. gattii infection in mice. BALB/c mice immunized with C. gattii CW and/or CP protein preparations exhibited a significant reduction in pulmonary fungal burden and prolonged survival following pulmonary challenge with C. gattii. Protection was associated with significantly increased pro-inflammatory and Th1-type cytokine recall responses, in vitro and increased C. gattii-specific antibody production in immunized mice challenged with C. gattii. A number of immunodominant proteins were identified following immunoblot analysis of C. gattii CW and CP protein preparations using sera from immunized mice. Immunization with a combined CW and CP protein preparation resulted in an early increase in pulmonary T cell infiltrates following challenge with C. gattii. Overall, our studies show that C. gattii CW and CP protein preparations contain antigens that may be included in a subunit vaccine to induce prolonged protection against pulmonary C. gattii infection.